ROBUST POLITICAL ECONOMY AND THE PRIORITY OF MARKETS. Issue 1 (14th June 2017) - Pennington, Mark
Abstract: This essay offers a "nonideal" case for giving institutional priority to markets and private contracting in the basic structure of society. It sets out a "robust political economy" framework to examine how different political economic regime types cope with frictions generated by the epistemic limitations of decision-makers and problems of incentive incompatibility. Focusing on both efficiency arguments and distributive justice concerns the essay suggests that a constitutional structure that prioritizes consensual exchange is more likely to sustain a cooperative venture for mutual advantage.